EFEKTIVITAS PENERAPAN MANAJEMEN ASN TERHADAP SISTEM INFORMASI KINERJA PEGAWAI (SINERGI) DI KOTA PEKANBARU TAHUN 2020-2021 - Virgo Prima Sitompul; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Employee Performance Information System (SINERGI) is a performance management information system in order to assess employee performance more measurably and objectively in the Pekanbaru City Environment which serves as the basis for realizing SKP and the basis for paying TPP. The problem in this research is that the implementation of SINERGI in Pekanbaru City has not been optimal due to several determining factors that underlie the readiness for the implementation of SINERGI that does not run effectively. The purpose of this study was to determine the effectiveness of the implementation of SINERGI in Pekanbaru City in 2020-2021. This research approach uses a qualitative approach. This type of research is descriptive research. The location of this research is in Pekanbaru City. The types and sources of research data are divided into primary data with purposive and secondary data in the form of supporting data related to SINERGY. The results of this study are that the implementation of SINERGI in Pekanbaru City Year 22020-2021 is quite effective, but there are still employees who have not achieved the SKP target. SINERGI fosters a sense of responsibility for employees for their duties and obligations as public servants and assesses employee performance more measurably and validated so that employees feel satisfied with their performance. The inhibiting factors for the implementation of SINERGI in Pekanbaru City are the lack of employee awareness in the use of SINERGI, lack of socialization, guidance, and information about SINERGI, and problems with the network and server so that the use of SINERGI does not work well. Keywords : Effectiveness , SYNERGY, Employees